The Italian PrEPventHIV challenge: a scoping systematic review on HIV pre-exposure prophylaxis monitoring in Italy - Ferrara, Pietro; Gianfredi, Vincenza (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: In Italy, pre-exposure prophylaxis (PrEP) with emtricitabine and tenofovir disoproxil fumarate (FTC/TDF) was authorized for HIV prevention in 2017. This scoping systematic review summarizes current evidence on PrEP implementation in Italy since 2017.Methods: A systematic search was conducted in relevant databases, using a search strategy built upon controlled vocabulary, cross-referencing of the citation lists from included reports, and hand-searching of surveillance documents. Findings were summarized narratively according to key issues and themes.Results: A total of 106 reports were retrieved and six met criteria for inclusion in the review, being three journal articles and three surveillance report by the European Centre for Disease Prevention and Control (ECDC). In Italy, users can obtain in PrEP in specific hospital- or community-based PrEP services, under prescription by specialists. Due to drug costs, the access is limited to those who can afford it. Data and indicators on PrEP use and monitoring are limited. The vast majority of users were men who have sex with men. In this population, PrEP knowledge and attitudes were investigated across two reports, finding a medium to high level to knowledge and a scare use (mostly due to high costs). A health technology assessment on the adoption of PrEP in Italy advised that the most cost-containing strategy would be the use of PrEP as an “add-on” strategy.Conclusions: In conclusion, this scoping review found a relevant evidence gap on PrEP monitoring. Italy needs to implement specific policies and programs for effective and timely delivery of care.